Web Based Banker Algorithm Simulation - Bintang Rakha Daniswara; Rodrick Kiedies; Joshua Warman Sigalingging; gatot santoso (Penerbitan Universitas Trisakti, 2023)
This study aims to analyze and evaluate the Banker algorithm, which is used in operating systems to manage resources in a multiprogramming computing environment. This study uses an analytical and experimental approach to study the performance of the Banker algorithm in managing resource allocation and preventing deadlock conditions. The data was obtained through computer simulations and statistical analysis was used to compare results with other resource allocation algorithms. This research is expected to provide useful insights for operating system designers in selecting and implementing efficient algorithms to manage resources in complex computing environments.